Development of an Enyne Metathesis/Isomerization/Diels–Alder One‐Pot Reaction for the Synthesis of a Novel Near‐Infrared (NIR) Dye Core. Issue 48 (9th October 2015) - Yamashita, Kohei; Fujii, Yuki; Yoshioka, Shohei; Aoyama, Hiroshi; Tsujino, Hirofumi; Uno, Tadayuki; Fujioka, Hiromichi; Arisawa, Mitsuhiro
Abstract: N ‐Alkyl‐ N ‐allyl‐2‐alkynylaniline derivatives undergo a tandem ring‐closing enyne metathesis/isomerization/Diels–Alder cycloaddition sequence in the presence of a second‐generation Grubbs catalyst and dienophiles. In practice, the acyclic enyne in the presence of the ruthenium alkylidene first undergoes ring‐closing metathesis to generate cyclic 4‐vinyl‐1, 2‐dihydroquinolines; following diene isomerization and then the addition of a dienophile, these ring‐closing metathesis products are selectively converted into a 7‐methyl‐4 H ‐naphtho[3, 2, 1‐ de ]quinoline‐8, 11‐dione core. Overall, the reaction sequence converts simple aniline derivatives into π‐conjugated small molecules, which have characteristic absorption in the near‐infrared region, in a single operation through three unique ruthenium‐catalyzed transformations. Abstract : In the red! N ‐Alkyl‐ N ‐allyl‐2‐alkynylaniline derivatives undergo a tandem ring‐closing enyne metathesis/isomerization/Diels–Alder cycloaddition sequence in the presence of a second‐generation Grubbs catalyst and dienophiles (see scheme). Overall, the reaction sequence converts simple aniline derivatives into π‐conjugated small molecules, which have characteristic absorption in the near‐infrared region, in a single operation through three unique ruthenium‐catalyzed transformations.